2021
DOI: 10.1002/mbo3.1227
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic potential of the imperfect denitrifier Candidatus Desulfobacillus denitrificans in an anammox bioreactor

Abstract: The imperfect denitrifier, Candidatus (Ca.) Desulfobacillus denitrificans, which lacks nitric oxide (NO) reductase, frequently appears in anammox bioreactors depending on the operating conditions. We used genomic and metatranscriptomic analyses to evaluate the metabolic potential of Ca. D. denitrificans and deduce its functional relationships to anammox bacteria (i.e., Ca. Brocadia pituitae). Although Ca. D. denitrificans is hypothesized to supply NO to Ca. B. pituitae as a byproduct of imperfect denitrificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The genus Rugosibacter was not taken into consideration in the proposal of Sterolibacteriaceae, and it is still placed in the family Rhodocyclaceae as noted in the original description. The close relatedness between Rugosibacter and genera of Sterolibacteriaceae has also been indicated by a phylogenetic analysis of concatenated ribosomal proteins (Okubo & Takami, 2021).…”
Section: Introductionmentioning
confidence: 94%
“…The genus Rugosibacter was not taken into consideration in the proposal of Sterolibacteriaceae, and it is still placed in the family Rhodocyclaceae as noted in the original description. The close relatedness between Rugosibacter and genera of Sterolibacteriaceae has also been indicated by a phylogenetic analysis of concatenated ribosomal proteins (Okubo & Takami, 2021).…”
Section: Introductionmentioning
confidence: 94%
“…Previous studies have elucidated the crucial functions of the phylum Chloro exota (e.g., the core genera UBA12294 and OLB14) in anammox microbiota [71][72][73]. However, previous studies underestimated the signi cance of several core taxa associated with the phylum Proteobacteria [20,74]. Here, we conducted a comparative genomic analysis to reveal the global pro les of the strict core genera Desulfobacillus and Zeimonas (Additional le 2: Tables S24-S25).…”
Section: Diversity Of the Genera Desulfobacillus And Zeimonas In Anam...mentioning
confidence: 99%
“…S18-S20). Importantly, six predominant species within the genus Desulfobacillus carried the hydroxylamine oxidoreductase gene (hao), whereas most lowabundance and reference species had lost this crucial gene responsible for NO and/or hydroxylamine production [74]. The absence of the nitric oxide reductase gene (norB) indicated that the genus Desulfobacillus may serve as a potential N 2 O sink in anammox microbiota.…”
Section: Diversity Of the Genera Desulfobacillus And Zeimonas In Anam...mentioning
confidence: 99%
See 1 more Smart Citation